2015
DOI: 10.17221/7923-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Cloprostenol and eCG influence oestrus synchronisation and uterine development in mice

Abstract: ABSTRACT:The aim of this study was to investigate the efficacy of equine chorionic gonadotropin (eCG) and cloprostenol (CLO) administration on oestrus synchronisation, uterine development as well as serum LH and FSH concentrations in mice. One hundred and five KM mice were assigned into eCG-1, eCG-2, eCG-3, CLO-1, CLO-2, CLO-3 and control groups (CG, n = 15). The eCG-1, eCG-2 and eCG-3 groups were intramuscularly injected with 10, 20 and 40 IU eCG. CLO-1, CLO-2 and CLO-3 were intramuscularly injected with 10, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…However, these results were not achieved in guinea pig (Grégoire et al, ) or agouti, showing limitations in oestrous induction (Peixoto et al, ). In addition, research has shown that the administered dose of this hormone may affect oestrous synchronization efficiency (Wei et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these results were not achieved in guinea pig (Grégoire et al, ) or agouti, showing limitations in oestrous induction (Peixoto et al, ). In addition, research has shown that the administered dose of this hormone may affect oestrous synchronization efficiency (Wei et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Gonadotropins such as FSH and eCG have been used for ovarian stimulation protocols in several species, but have never been tested in large rodents. Comparing those hormones in superovulation protocols, it was observed that mice responded better to eCG than to FSH (Corbin & McCabe, ) which showed to be very effective for both oestrous induction and ovarian hyperstimulation (Agca, Yakan, & Agca, ) especially if combined with cloprostenol (Wei et al, ). However, FSH and eCG showed similar efficiency in some rat strains (Popova, Bader, & Krivokharchenko, ).…”
Section: Discussionmentioning
confidence: 99%
“…It is recommended that prostaglandin F 2 -alpha (PGF 2 α), alone or in combination with a hormone that stimulates follicle development, be used as a luteolytic agent to increase reproductive efficiency and the pregnancy rate. However, this is generally costly and may not produce the expected effect in some cases (11,27).…”
Section: Praca Oryginalnamentioning
confidence: 99%
“…Cloprostenol is a potent PGF 2 α analogue. Therefore, reproduction may be controlled by the lysis of the corpus luteum and by inducing a subsequent follicular phase with ovulation (27). Equine chorionic gonadotropin, which is a gonadotropic hormone produced in the chorion of pregnant mares, is widely used to obtain a large number of oocytes by the induction of superovulation in many animals (13,(18)(19)(20)(21)25).…”
Section: Praca Oryginalnamentioning
confidence: 99%
See 1 more Smart Citation